The Lithological Features of Sublacustrine Fans and Significance to Hydrocarbon Exploration: A Case Study of the Chang 7 Interval of the Yanchang Formation, Southeastern Ordos Basin, North China. (8th May 2021) - Yang, Bo; Qu, Hongjun; Shi, Jianchao; Bai, Yuqi; Li, Wenhou; Zheng, Yanrong; Zhang, Rongjun
Abstract : The Chang 7 interval of the Upper Triassic Yanchang Formation in the Ordos Basin represents a typical deep lacustrine depositional sequence. On the basis of field outcrops, cores, well logs, light/heavy mineral provenance analysis, and petrological studies, we evaluated the characteristics of deep-water gravity flow deposition of the Chang 7 interval and constructed a depositional model. The sediments mainly came from the northeast of the study area, and multiple sublacustrine fans were deposited in the center of the basin. Different from the deep-marine fan, the sublacustrine fan in the study area develops under the background of gentle slope without any erosional canyon between the fan and delta front. Gravity flow deposits in the study area can categorised into three groups: sand debris flow deposits, turbidity current deposits, and deep-water mudstone deposits. The main channel and branch channel are mainly developed with thick massive sandy debris sandstone, while the channel lateral margin and branch channel lateral margin are mainly developed with middle massive sandy debris sandstones and turbidite sandstones, which from bottom to top, the thickness of sand layer becomes thinner and the grain size becomes smaller. Thin mudstone is developed between channels; the lobe fringe includes sheet-like turbidite sandstones and deep lake mudstones. The widely distribute, good quality source rocks (TOC = 2 % – 6 % ) developed in deep lacustrine have attained the peak stage of oil generation (R o = 0.9 % – 1.2 % ). The superimposition of the sublacustrine fan sand bodies and the wide distribution of good quality source rocks favor the formation of large lithologic reservoirs characterized by source–reservoir integration, self-generation and self-storage, and near-source accumulation.